El mandril de madame Blavatsky : historia de la teosofía y del gurú occidental / Peter Washington ; [traducción, José Luis Fernández-Villanueva] - Fernández Villanueva, José Luis; Washington, Peter (Oráculo manual ; 2)
Bibliografía: p. 419-429. Índice de nombres